Sexual behaviours and contraceptive usage among Nigerian undergraduates: Moderating effects of course of study and school type - Akinduyo, Tosin. E.; Mabaso, N.P.M (Educenter : Jurnal Ilmiah Pendidikan, 2024)
Sexual behaviours and contraceptive usage among undergraduates are sources of concern to all stakeholders in Nigeria and across the globe. This study addresses the gap by investigating the roles of school type (i.e., private and public and the faculty/course of study on undergraduates’ sexual behaviours and contraceptive usage among undergraduates in Southwestern part of Nigeria. This quantitative study used a descriptive design of the survey type. One thousand and two hundred (1,200) undergraduates were selected for this study using multi-stage sampling technique. Results showed that many undergraduates in different kinds of sexual behaviours such as penetrative sex, embracing the opposite sex, dating, petting and kissing; with only undergraduates from private tertiary institutions and studying health-related course were acquainted with the adequate use of contraceptives. Based on the findings of this study, it was recommended that increased awareness should available for undergraduates across all agents of socialization to prevent health-risk challenging the well-being of undergraduates.